2016
DOI: 10.3390/ijms17101762
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Toxicity of Selected Personal Care Products Using Embryo Bioassays: 4-MBC, Propylparaben and Triclocarban

Abstract: Recently, several emerging pollutants, including Personal Care Products (PCPs), have been detected in aquatic ecosystems, in the ng/L or µg/L range. Available toxicological data is limited, and, for certain PCPs, evidence indicates a potential risk for the environment. Hence, there is an urgent need to gather ecotoxicological data on PCPs as a proxy to improve risk assessment. Here, the toxicity of three different PCPs (4-Methylbenzylidene Camphor (4-MBC), propylparaben and triclocarban) was tested using embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
3
23
1
2
Order By: Relevance
“…PP could also induce hatching delay by reducing hatching enzyme activities. Sublethal alterations recorded in our study were comparable with those reported in a previous study on zebrafish early‐life stages in which malformations appeared at a concentration of 3.5 mg/L at 32 hpf (Torres et al, ). In this study, the periods of observation were different from ours; in fact, embryos were observed just at three different developmental times (8, 32 and 80 hpf).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PP could also induce hatching delay by reducing hatching enzyme activities. Sublethal alterations recorded in our study were comparable with those reported in a previous study on zebrafish early‐life stages in which malformations appeared at a concentration of 3.5 mg/L at 32 hpf (Torres et al, ). In this study, the periods of observation were different from ours; in fact, embryos were observed just at three different developmental times (8, 32 and 80 hpf).…”
Section: Discussionsupporting
confidence: 91%
“…PP was dissolved in DMSO (DMSO at final concentration of 0.1%) and tested at five concentrations (1, 2, 4, 6, 8 mg/L). Experimental concentrations were chosen based on available literature (Torres, Cunha, Martins, & Santos, ). Selected embryos were placed individually with 2 mL of solution in each well of 24‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Embryogenesis studies were carried out with slight modification of OECD TG236 (OECD, 2013 and Torres et al (2016). During the reproductive trials, 15 embryos from each treatment sub-replicate, with 1-1.5 hpf, were kept and randomly placed in 24 well plates (one egg per well) with 2 ml of clean dechlorinated water, free of SIM (Figure 1.B).…”
Section: Methodsmentioning
confidence: 99%
“…The 24 well plates were randomly maintained on a water bath at 26.5 ± 0.5°C during 80 h. Embryos were checked, every day, for mortality and at the end of the assay (80 hpf) were observed, under a stereomicroscope, for embryo development analysis. Morphological abnormalities on eyes, head, tail or yolk-sac; pericardial oedema; abnormal cell growth and developmental arrest were recorded as present or absent (Torres et al, 2016). Heart rate was evaluated during 15 s in four embryos per plate using a stop-watch, restarting the counting if the embryo moved.…”
Section: Methodsmentioning
confidence: 99%
“…Other adverse effects of TCC, such as hepatotoxicity, renal toxicity, and gene toxicity, have also been reported for different species. Exposure to 350 μg/L TCC was recently reported to induce an approximately 75% mortality rate; exposure to 133.3 and 147.5 μg/L TCC also decreased the heart rate and delayed yolk absorption and swim bladder development in zebrafish embryos from 6 hours post fertilization (hpf) to 120 hpf . Furthermore, exposure to 6.7 μg/L TCC altered protein expressions related to binding and metabolism and skeletal muscle development and function and those involved in nervous system development and immune response, indicating that TCC features potential health risks in wildlife and humans at low concentration levels .…”
Section: Introductionmentioning
confidence: 99%